(untitled) (Analele Universității București. Limba și literatură română, 2024)
This is the second part of a more general research on the comparison between Differential (Direct) Object (DOM) and Differential Agent Marking (DAM) in (contemporary) Romanian. Previously, I have showed that DOM is an optional phenomenon (with a few exceptions for certain types of Direct Objects). DOM is sensitive to factors like animacy, specificity, and topicality. In the present study, I will show that DAM is only sensitive to animacy, but neither to specificity nor to topicality. Additionally, DAM seems to be affected by language register, namely the official / administrative one.